Prehatch Calls and Coordinated Birth in Turtles - Gabriel Jorgewich‐Cohen; Madeleine Wheatley; Lucas Pacciullio Gaspar; Peter Praschag; Nicole Scholte Lubberink; Keesha Ming; Nicholas A. Rodriguez; Camila R. Ferrara (Ecology and Evolution)
ABSTRACT Hatching synchronisation is widespread in oviparous taxa. It has been demonstrated that many species use sounds to coordinate synchronous hatching, being widespread among archosaurs (birds and crocodilians). Recent studies have shown that some turtle species produce vocalisations from within the egg, but the role of this behaviour in synchronising hatch is untested. The small amount of information about sound production by turtle embryos, limited to a handful of closely related species, precludes any inferences based on differences in their ecology, reproductive behaviour and phylogenetic context. With the goal to investigate if coordinated synchronous behaviour is mediated by within‐egg vocalisations in turtles, we recorded clutches from six different turtle species. The selected animals present different ecological and reproductive niches and belong to distinct phylogenetic lineages at the family level. We aimed to understand: (1) what is the phylogenetic distribution of within‐egg vocal behaviour among turtles; (2) if asynchronous turtle species vocalise from within the egg; (3) if clutch size influences synchronous behaviour and (4) if within‐egg turtle calls follow any phylogenetic signal. The new evidence provides light to the current knowledge about synchronous behaviour and within‐egg calls, challenging previous hypothesis that within‐egg sounds are accidentally produced as side‐effects of other behaviours.